Bringing AI to the edge: a formal M&S specification to deploy effective IoT architectures. Issue 5 (3rd September 2022) - Cárdenas, Román; Arroba, Patricia; Risco Martín, José L.
ABSTRACT: Internet of Things applications are based on ubiquitous networks of multiple distributed devices, with limited computing resources and power, capable of collecting and storing data from heterogeneous sources in real-time. To avoid network saturation and delays, new architectures are needed to provide real-time Big Data and data analytics capabilities at the edge of the network, where energy efficiency needs to be considered to ensure a sustainable and effective deployment in areas of human activity. In this research, we present an IoT model based on the principles of Model-Based Systems Engineering. It covers the description of the entire architecture, from IoT devices to the processing units in edge data centres, and includes the location-awareness of user equipment, network, and computing infrastructures to optimise federated resource management in terms of delay and power consumption. We present a framework to assist the dimensioning and the dynamic operation of IoT data stream analytics applications.